The Cephalometrıc Evaluatıon Of The Effects Of Fränkel's Functıon Regulator (Fr-4) Wıth Lıp-Seal Traınıng In The Soft-Tıssue Profıle On The Treatment Of Angle Class I Skeletal Anterıor Open-Bıte Malocclusıon - Elif Erbay; Mustafa Ülgen (Galenos Yayinevi, 1993)
The present study attempts to evaluate cephalometrically the effects of Fränkel's function regulator (FR-4) appliance with the lip-seal training in the soft-tissue profile on the treatment of Angle Class I skeletal anterior open-bite malocclusions. Thirty-three patients (20 girls and 13 boys) with Angle Class I skeletal anterior open-bite, were randomly divided into the treated and the untreated groups. The investigation was carried out on 66 lateral cephalograms of taken prior to and after the study period. Chronological mean decimal age at the initial period of the investigation was 8.72 years in the treated group, and 8.79 years in the untreated group, their treatment and observation periods being 2 years. The results of the present study indicate that there was no significant difference between the changes taking place in the soft-tissue profile in the both groups.